Missed Opportunity of Antenatal Care Services Utilization and Associated Factors among Reproductive Age Women in Eastern Hararghe Zone, Eastern Ethiopia: Mixed Methods Study - Ibsa Mussa; On Makhubela-Nkondo; Melat B. Maruta; Adera Debella (Journal of Pregnancy)
Background. Despite the enormous advantages of early pregnancy-related problem diagnosis and therapy during prenatal care visits, not all pregnant women begin antenatal care at the proper time. Thus, this study aims to identify factors associated with missed opportunities for antenatal care service utilization among reproductive-age women in Eastern Ethiopia. Methods. A mixed methods study design (quantitative and qualitative) was conducted in Grawa, Meta, and Haramaya woredas from September 5 to December 5, 2019. The quantitative data were analyzed using SPSS version 25. A multivariable logistic regression analysis model was used to identify the predictors. Statistical software programs based on ATLAS.ti version 8.2 was were used to conduct the thematic analysis of the qualitative data. Results. Overall, missed opportunities for antenatal care were 15.4% of 95% (12.1, 19.1%). Factors such as maternal age being 15–24 (AOR=6.9, 95% CI: 2.89–8.81); having a college education (AOR=0.02, 95% CI: 0.001, 0.42), elementary (AOR=0.05, 95% CI: 0.002, 0.98), and secondary education (AOR=0.04, 95% CI: 0.001, 0.88); having five and more parity (AOR=0.08, 95% CI: 0.01, 0.75); three visits (AOR=0.10, 95% CI: 0.02, 0.71); those in the first trimester (AOR=0.02, 95% CI: 0.001, 0.35) and the second trimester (AOR=0.01, 95% CI: 0.001, 0.26); and get information from a health facility (AOR =0.09, 95% CI: 0.01, 0.67) and traditional birth attendance (AOR=0.02, 95% CI: 0.001, 0.74) were factors statistically associated with outcome variables. Conclusions. According to this report, relatively high proportions of pregnant women experienced missed opportunities in antenatal care follow-up. Factors such as maternal age, education, parity, frequency, timing, and media access were statistically significantly correlated with missed antenatal care follow-up. Therefore, all stakeholders should emphasize advocating for and enhancing the benefits of antenatal care; this in turn plays a crucial role in increasing the follow-up of clients for these crucial services. Moreover, health policy implementers need to coordinate their tracking of pregnant women who missed their antenatal care session.